Preparedness and Practice Competency in Tracheostomy Management by Speech language Pathologists in Saudi Arabia - Abdul Samadh, Shabeer Ali; Aljabali, Muhannad (J Med Rehab Sci, 2024)
The scope of practice by Speech language pathologists in tracheostomy management in patients with or without mechanical ventilation is continuously expanding. Despite this expanding scope, less is known on what is being done throughout the SLPs academic and professional practice in order to achieve competencies and quality practice. This study aimed to identify the preparations, clinical consistencies and current practice patterns among the Speech language pathologists while treating tracheostomy patients with and without mechanical ventilator within the kingdom of Saudi Arabia. The questionnaire adapted with approval from the authors, Ward et al., (2007, 2008 and 2012) and McGowan et al, (2014). Thirty-eight Speech language pathologists working in Saudi Arabia responded to this survey. Results revealed low consensus in clinical practice patterns of the speaking valve fitting in ventilated patients, decision making of the type of tracheostomy tube and decannulation recommendations; whereas moderate consensus expressed in using speaking valve in tracheostomy patients without mechanical ventilator and dysphagia management in such patients. The findings of this study warrant the need to establish an academic based training program, formal multidisciplinary team and clinical care pathway in respective institutions and hospitals for timely referral and managements of tracheostomy patients with and without mechanical ventilation. This study advocates the respective professional governing body to announce a position statement for managing tracheostomized patients and need for periodic training or continuing professional educations to enhance the preparedness of the Speech language pathologists in Saudi Arabia.